2021
DOI: 10.3390/app11072921
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Lactobacillus paracasei CBA L74 Growth during Rice Flour Fermentation Performed with and without pH Control

Abstract: The mathematical modeling of fermentation processes allows for the formulation of predictions about the kinetics of biomass growth and metabolite production as well as setting or verifying the best operative conditions in view of the economical convenience of the process. For this purpose, we performed a kinetic study of a rice flour fermentation process using Lactobacillus paracasei CBA L74 with and without pH control; the pH value was set to 5.8 under pH control. Monod, Logistic, and Contois models were prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Most of these types of functional foods are dairy-based products [20][21][22], but products of a different nature are also on the rise. The ability of the bacterial strain that was used in the present study to ferment food matrices, such as cereals and legumes, has previously been demonstrated [17,[23][24][25][26][27][28][29], and its probiotic activity has also been confirmed in previous studies [30][31][32][33]; in the present work, its ability to ferment an industrial product, such as banana puree, was investigated. Banana, both as a fresh or processed fruit, is one of the most consumed fruit crops worldwide, starting from infancy.…”
Section: Discussionmentioning
confidence: 60%
“…Most of these types of functional foods are dairy-based products [20][21][22], but products of a different nature are also on the rise. The ability of the bacterial strain that was used in the present study to ferment food matrices, such as cereals and legumes, has previously been demonstrated [17,[23][24][25][26][27][28][29], and its probiotic activity has also been confirmed in previous studies [30][31][32][33]; in the present work, its ability to ferment an industrial product, such as banana puree, was investigated. Banana, both as a fresh or processed fruit, is one of the most consumed fruit crops worldwide, starting from infancy.…”
Section: Discussionmentioning
confidence: 60%
“…Conversely, th mum bacterial load of 9.48 log (CFU/g) found by controlling pH was similar achieved during the uncontrolled pH process (9.74 log(CFU/g) [28]. Furtherm demonstrated by Colucci Cante et al [34], pH control allows the microorganism t a better duplication capacity and improved kinetic performances.…”
Section: Fermentation Resultsmentioning
confidence: 80%
“…The fermentation process was carried out on a hydrolyzed oatmeal suspension under controlled conditions of temperature and pH, previously identified as optimal for LP's growth and its metabolic activity [34,35], and a subsequent mild heat treatment was performed to achieve the microbial inactivation. The effect of each single process step on selected functional properties of interest, as lactic acid concentration, total polyphenol content, antioxidant activity, anti-tyrosinase activity, and photoprotection activity (Sun Protection Factor, SPF, estimation) was investigated to confirm the potential of the resulting oat-based postbiotic.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) and Colucci Cante et al. (2021) studied the impact of controlling pH at an optimal value of 5.8 on the growth kinetics and the lactic acid production during a rice flour fermentation process using Lacticaseibacillus paracasei CBA L74.…”
Section: Fermentation As a Tool For Enhancing Gut‐healthy Compoundsmentioning
confidence: 99%